Value of a novel Y-Z magnetic totally implantable venous access port in improving the success rate of one-time needle insertion - Zhang, Miaomiao; Lyu, Xin; Wang, Juanjuan; Shi, Aihua; Zheng, Yunyun; Lyu, Yi; Yan, Xiaopeng (Frontiers in Surgery, 2023)
Background and objectives: A totally implantable venous access port (TIVAP) is a commonly used intravenous infusion device for patients receiving chemotherapy or long-term infusion therapy. To improve the success rate of one-time insertion of the Huber needle, we developed a novel Y-Z magnetic TIVAP (Y-Z MTIVAP), which we produced using three-dimensional printing technology. Materials and methods: The Y-Z MTIVAP includes a magnetic port body and a magnetic positioning device. For testing, we established four venous port implantation models using the two types of TIVAPs and two implantation depth ranges (≤5 mm and >5 mm). Twenty nurses performed Huber needle puncture with the four models, and we recorded the number of attempts required for successful needle insertion, the operation time, and the operator’s satisfaction. Results: The success rate for one-time needle insertion with the Y-Z MTIVAP was significantly higher than that with the traditional TIVAP at either depth range (100% vs 75% at ≤5 mm, p=0.047; 95% vs 35% at >5 mm, p<0.001). With increasing implantation depth, the success rate for one-time insertion was significantly reduced with the traditional TIVAP (75% at ≤5 mm vs 35% vs >5 mm, p=0.025), but the success rate with the Y-Z MTIVAP was not significantly affected (100% vs 95%, p=1.000). The operation time with the Y-Z MTIVAP was significantly shorter than that with the traditional TIVAP at either depth range (both p<0.001), and 90% of operators reported that the Y-Z MTIVAP was superior to the traditional TIVAP. Conclusions: The theoretical design of Y-Z MTIVAP is feasible, and the preliminary in vitro simulation experiment shows that it can significantly improve puncture success rate and shortened operation time.